Identifying potential spoilage markers in beef stored in chilled air or vacuum packaging by HS-SPME-GC-TOF/MS coupled with multivariate analysis. (September 2019) - Mansur, Ahmad Rois; Seo, Dong-Ho; Song, Eun-Ji; Song, Nho-Eul; Hwang, Sun Hye; Yoo, Miyoung; Nam, Tae Gyu
Abstract: Volatile organic compounds (VOCs) associated with spoilage are attracting the attention as potential markers for monitoring meat quality. The objective of the present study was to evaluate the use of spoilage-associated VOCs as marker compounds for the assessment of beef spoilage during storage at 4 °C in air and when vacuum packed. We used headspace solid-phase microextraction coupled with gas chromatography time-of-flight mass spectrometry to determine the levels of VOCs formed during storage. Correlation analysis and multivariate analyses (principal component and hierarchical clustering analysis) were used to select several VOCs that most contribute to sensory changes, and to classify beef samples based on the degree of spoilage assessed by sensory panelists, respectively. Levels of acetic acid, ethanol, 2-methylbutan-1-ol, 3-methylbutan-1-ol, 2, 3-butanediol, 2-butanone, diacetyl, 2-heptanone, 3-octanone, and acetoin significantly ( p  < 0.05, p  < 0.01) correlated with the spoilage of air-stored beef, while acetic acid, butanoic acid, pentanoic acid, ethanol, 3-methylbutan-1-ol, and 2, 3-butanediol significantly ( p  < 0.05, p  < 0.01) correlated with the spoilage of vacuum-packed beef. The multivariate-analysis results reveal that the aforementioned VOCs can be used as potential marker compounds for evaluating beef spoilage during chilled storage in air or when vacuum packed. Highlights: Beef spoilage was evaluated on the basis of volatile organic compounds (VOCs). Air and vacuum-package storage affect VOC production in chilled beef differently. VOCs associated with sensory changes are useful for the evaluation of beef spoilage.